2007
DOI: 10.1042/bst0351180
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid metabolism, insulin secretion and diabetes

Abstract: In addition to the primary stimulus of glucose, specific amino acids may acutely and chronically regulate insulin secretion from pancreatic beta-cells in vivo and in vitro. Mitochondrial metabolism is crucial for the coupling of glucose, alanine, glutamine and glutamate recognition with exocytosis of insulin granules. This is illustrated by in vitro and in vivo observations discussed in the present review. Mitochondria generate ATP (the main coupling messenger in insulin secretion) and other factors that serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
148
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 54 publications
9
148
0
5
Order By: Relevance
“…An upstream open reading frame suppresses translation of Ucp2 mRNA [41]. Glutamine, which has been implicated in the insulin secretion pathway [42], overcomes this suppression [43]. Removal of glutamine from INS-1E cell cultures rapidly halves both cellular and mitochondrial UCP2 protein content without affecting the Ucp2 mRNA level ( figure 3) [12].…”
mentioning
confidence: 99%
“…An upstream open reading frame suppresses translation of Ucp2 mRNA [41]. Glutamine, which has been implicated in the insulin secretion pathway [42], overcomes this suppression [43]. Removal of glutamine from INS-1E cell cultures rapidly halves both cellular and mitochondrial UCP2 protein content without affecting the Ucp2 mRNA level ( figure 3) [12].…”
mentioning
confidence: 99%
“…The presence of glutamate concentration proved the consumption of glutamine in BRIN-BD11 cells in T-flask and MC cultures. Newsholme et al (2007) reported in their study that although glutamine was rapidly taken up and metabolized by the cells, it alone did not stimulate insulin secretion or enhanced glucose-induced insulin secretion. This observation is supported by the study done by Zahid et al (2008) and Newsholme et al (2007) that combination of D-glucose and L-glutamine promote good cell growth and insulin secretion of BRIN-BD11 cells as a step towards mass propagation of insulin production.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, faster cell growth rate observed in HIIMCs is attributed to its surface charge that supports easy attachment of cells and easy detachment with trypsin (Varani et al 1998). Newsholme et al (2007) reported that the major physiological regulator in insulin production is glucose. Based on the results in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that high levels of amino acids can have both positive (Tremblay and Marette, 2001;Nobukuni et al, 2005) and negative (Armstrong et al, 2001;Bogan et al, 2001) effects on glucose metabolism and insulin action in peripheral tissues. Amino acid levels can also affect insulin secretion in pancreatic islet β-cells (Newsholme et al, 2007). Therefore, it is possible that S-nitrosation interferes with amino acid metabolic processes and thus contributes to diabetes.…”
Section: Discussionmentioning
confidence: 99%